DE-RADIKALISASI AGAMA DAN PENDIDIKAN KEARIFAN LOKAL PADA MAHASISWA UNIVERSITAS ANDI DJEMMA DI KOTA PALOPO - Zainuddin, Fauziah (PALITA, 2016)
Abstract:This article discussed the perceptions of Administration Department students at AndiDjemma University of Palopo on religious de-radicalization and local wisdom as well as theroles of local wisdom education among the students. To answer these problems, it surveyed 50Out of 150 students of Administration Department at Andi Djemma University of Palopo. It wasfound that; a) the studentsâ perception level on local wisdom was categorized moderate. Thiscategory means that the respondents simply knew the terms of local wisdom based on theirnative language labeled, not the meaning or the substances. b) The studentsâ perception levelon radicalism and de-radicalization was categorized moderate. This category tends to be closeto radical. It means that the students conceptually knew about modern religious views thatare rational and fundamental. However, they did not realize as a form of radicalism. c) Thestudentsâ perception level on the roles of local wisdom education regarding the deradicalizationwas categorized well. It means that the lecturers integrated the local wisdom inthe learning process. It adequately contributed to the development of studentsâ thinking thatserves as a comparison in counteracting radical ideology to reach the consciousness ofhumanity.